Urbanization, climate change and health vulnerabilities in slum communities in Ghana - Enoch Damte; Bob Offei Manteaw; Charlotte Wrigley-Asante (The Journal of Climate Change and Health, 2023)
Introduction: Rapid population growth, increased migration, surge urbanization and human settlement challenges have become defining features of most African cities. Accra, the capital of Ghana, is no exception as its fast-urbanizing processes and associated housing challenges have seen the emergence of slum communities in and around the city. While slum communities are not new in Accra nor in Ghana, what is worrying is the current pace of emergence, the state of such communities, population density and levels of vulnerability. Even more worrying are the observed impacts of climate-induced extreme weather events on such communities and attendant health consequences. Methodology: Focusing on some slum communities in and around the city of Accra, this paper investigates the environmental health conditions of slum communities and how such conditions converge with climate change impact manifestations to increase disease burden. The paper employed a concurrent triangulation mixed method approach to simultaneously gather data from randomly selected slum communities in the Accra Metropolitan Assembly and La-Nkwantanang Madina municipality to explore possible correlations between current changes in climate and public health challenges. Conclusion: The results affirm a correlation between observed climate change impacts and prevailing health conditions in the selected slum communities. There is ample evidence to signal both direct and indirect linkages between climate-induced weather events and increased prevalence of diseases such as malaria, diarrhea, cholera, skin disease, lung diseases, as well as the emergence of novel diseases in the target slum communities. The study, ultimately, succeeds in demonstrating the nexus of climate change, health, and urbanization.